STATISTICAL SAMPLING IN THE AUDIT OF THE AIR FORCE MOTOR VEHICLE INVENTORY. - Cyert, R. M.; Hinckley, G. M.; Monteverde, R. J. (The Accounting Review, 1960)
The significance of survey sampling as a useful tool for accounting has become more apparent in recent years. There is increasing evidence that accountants should become familiar with the characteristics of the various sample designs. It has been argued that the methods of statistical sampling can benefit accountants and auditors in two ways. First, the methods permit them to make' mathematically supportable estimates of Universe characteristics and second, because sampling is used in lieu of 100 percent count or itemization, the timeliness of reports to management can be increased. This article reports on one such instance, the verification of a physical inventory of motor vehicles of the U. S. Air Force by the Auditor General of the U. S. Air Force. The system for controlling and reporting vehicles within the Air Force is quite strong if it is followed. Essentially, the system requires that, at the time of procurement, a registration number will be assigned by the vehicle prime depot and a permanent registration card will be prepared in triplicate.